Analysis of the impact of clinical practices on salivary biomarkers of inflammation and stress in oral surgery postgraduate students: a pilot study - Barrientos-Moral, Laura; Gimeno-Longas, María José; Obispo-Díaz, Cristina; Martín-Vacas, Andrea; Paz-Cortés, Marta Macarena; Aragoneses, Juan Manuel (Frontiers in Medicine, 2025)
AimTo assess through salivary biomarkers if clinical practices generate stress and a systemic inflammatory response in dental surgery post-graduate students.Materials and methodsA cross-sectional analytical observational study was conducted with students from the Master’s in Clinical Dentistry program. Salivary samples were collected before and after surgical procedures to quantify stress (cortisol) and inflammation biomarkers (IL-6, IL-1β, and CRP). Additionally, students completed the Perceived Stress Scale (PSS) questionnaire prior to the surgical procedure. Descriptive and analytic statistics were conducted with a 95% significance level.ResultsA total analyzed sample included 21 subjects, with a mean age of 25.5 years. The influence of academic year, gender, or smoking status was none found to have a significant impact. The results show a significant decrease in cortisol levels between the pre- and post-measurements (mean difference = −108.2 ± 166.7). However, an increase in IL-6 levels was obtained (p < 0.05). High IL-6 levels were associated with elevated CRP levels. An inverse relationship was seen between perceived stress and salivary cortisol concentrations.ConclusionThe findings show a significant decrease in salivary cortisol (stress) levels and a significant increase in salivary IL-6 levels following a dental implantology procedure in postgraduate oral surgery students.